Desenvolvimento de sistemas adesivos empregando monômeros surfactantes como alternativa ao hidróxietil metacrilato (HEMA) - Zanchi, Cesar Henrique (2010)
This study evaluated the influence of surfactant dimethacrylates (SD) on the resin-to-dentin immediate and long term microtensile bond strength (μTBS) and characterized the interfacial micromorphology of hybrid layer of the experimental HEMA-free self-etching systems. Five experimental HEMA-free two step self-etching systems containing different surfactant dimetacrylates (SD) (Bis-EMA 10, Bis-EMA 30, PEG 400, PEG 1000 and PEG 400 UDMA) and a HEMA-containing systems (control) were formulated. Sixty bovine incisors were allocated into six groups according each experimental adhesive system used. The teeth had the superficial coronal dentins exposed and were restored and sectioned to obtain sticks randomly allocated into 3 storage periods: 24h, 6 and 12 months. Thereafter the specimens were subjected to the μTBS test. Immediate μTBS data were analyzed by One-way ANOVA and Tukey s test. Long term μTBS data were analyzed by Kruskall-Wallis and Dunn test (α = 0.05). Analysis of the adhesive-dentin interfaces were performed through scanning electron microscopy. Between the HEMA-free groups, the adhesive system formulated with PEG 400 UDMA produced the highest μTBS and was similar to HEMA-containing group. Specimens of the 24 hours of storage were statistically higher for all groups tested when compared those after 6 and 12 months storage. None difference was found between 6 months and 12 months storage for each group. All the adhesives systems presented similar partially demineralized hybrid layer (1.5-3.0 μm thickness) with well formed resin tags. All SD present reasonable μTBS, being the PEG 400 UDMA a promising monomer to be considered as HEMA substitute in adhesive systems compositions.